2023
DOI: 10.14740/jmc4137
|View full text |Cite
|
Sign up to set email alerts
|

Remimazolam for Sedation During Fiberoptic Intubation in an Adolescent

Mitchell Hughes,
Gregory Maves,
Joseph D. Tobias

Abstract: In specific clinical scenarios, fiberoptic intubation (FOI) may be the preferred technique for airway management and endotracheal intubation. In addition to topical anesthesia of the airway, sedation is frequently necessary, especially in younger patients, to facilitate the procedure. The goal is to facilitate the procedure by providing sedation, anxiolysis, and analgesia with maintenance of spontaneous ventilation. Remimazolam is a novel benzodiazepine with a short half-life and limited context sensitive half… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The short CSHT of remimazolam and its ease of titration by continuous infusion may make it an appropriate choice for sedation during FOI in children. Hughes et al 37 reported the successful use of remimazolam (15 µg/kg/min) and remifentanil (0.05 µg/kg/mi) for analgesia and sedation in a 12-year-old boy with postburn neck contracture and FOI was completed. This result suggests that the potential of remimazolam to preserve spontaneous breathing and rapidly reverse sedation is extremely important in patients who are difficult to intubate.…”
Section: Current Status Of Applications Of Remimazolammentioning
confidence: 99%
See 1 more Smart Citation
“…The short CSHT of remimazolam and its ease of titration by continuous infusion may make it an appropriate choice for sedation during FOI in children. Hughes et al 37 reported the successful use of remimazolam (15 µg/kg/min) and remifentanil (0.05 µg/kg/mi) for analgesia and sedation in a 12-year-old boy with postburn neck contracture and FOI was completed. This result suggests that the potential of remimazolam to preserve spontaneous breathing and rapidly reverse sedation is extremely important in patients who are difficult to intubate.…”
Section: Current Status Of Applications Of Remimazolammentioning
confidence: 99%
“…Flumazenil can quickly reverse the hypnotic effect of remimazolam, shorten the postoperative extubation time in children, allow spontaneous breathing after failed intubation and avoid delayed awakening in children with congenital metabolic diseases, which improves the safety and controllability of remimazolam anesthesia. 32 , 37 , 41 The FDA-approved doses of remimazolam for benzodiazepine reversal when used for pediatric patients (children 1 year and older and adolescents) receiving conscious sedation or general anesthesia are the initial dose of 0.01 mg/kg given over 15 seconds (up to a maximum dose of 0.2 mg). If no desired return of consciousness is noted after 45 seconds, repeat 0.01 mg/kg (up to 0.2 mg) at 1-minute intervals as needed.…”
Section: Current Status Of Applications Of Remimazolammentioning
confidence: 99%